TINGKAT PENGETAHUAN IBU RUMAH TANGGA TERHADAP PERILAKU PHBS DALAM TATANAN RUMAH TANGGA DI DESA SAINTIS - Nisa Mahfirah Lubis; Zuhrina Aidha; Nur'ainun Berutu (Lembaga Pengembangan Kinerja Dosen, 2023)
In order for the health and development of her family to be successful, a mother needs to have knowledge about clean and healthy living habits at home. PHBS was used by 53.9% of households in 2011, 56.5% in 2012, and 55.0% in 2013. This success is still far from what is needed. This study aims to find out how much housewives in Saintis village know PHBS behavior. A sample of 100 respondents was used in this research quantitative methodology. Based on the findings, 61% of respondents had sufficient knowledge, 22% had sufficient knowledge, and 17% had insufficient knowledge. As many as 42% of respondents showed good behavior, 49% showed moderate behavior, and 9% showed bad behavior. In Saintis village, most housewives already know about PHBS and behave accordingly, but some parents still don't understand or think too much about PHBS.